Long-lived transient anion of c-C4F8O - Kočišek, J; Janečková, R; Fedor, J (The Journal of chemical physics, 2018)
We report partial cross sections for electron attachment to c-C4F8O, a gas with promising technological applications in free-electron-rich environments. The dissociative electron attachment leads to a number of anionic fragments resulting from complex bond-breaking and bond-forming processes. However, the anion with the highest abundance is the non-dissociated (transient) parent anion which is formed around 0.9 eV electron energy. Its lifetime reaches tens of microseconds. We discuss the origin of this long lifetime, the anion's strong interactions with other molecules, and the consequences for electron-scavenging properties of c-C4F8O in denser environments, in particular for its use in mixtures with CO2 and N2.